2021
DOI: 10.1021/acs.jpcc.0c10187
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Transport in Engineered Hybrid Organic–Inorganic Perovskite Metasurfaces

Abstract: Halide perovskites have recently gained widespread attention for their exceptional optoelectronic properties, which have been illuminated by extensive spectroscopic investigations. In this study, nanophotonic surface engineering using a newly developed soft lithographic technique has been used to reproduce nanostructures with enhanced optical functionalities. The thermal sensitivity of the metasurfaces is first observed in the temperature-dependent photoluminescence (PL) spectra. In order to observe the local … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…In the radial heat wave example, the thermal conductivity can be expressed as K = α ( 1 2 πd ) true( normald P true) 1 where dω is the shift in the Raman peak position of the A 1g mode concerning the change in incident laser power d P on the material surface, α is the first-order temperature coefficient, and d is the thickness of the material. Shen et al and many other researchers demonstrated that the thermal conductivity of perovskite materials is independent of the thickness ( d ) in the range of 90 to 400 nm. , As a result, the influence of thickness “ d ” on thermal conductivity ( K ) may be considered to be insignificant. Thus, the only quantities to examine are α and (dω/d P ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the radial heat wave example, the thermal conductivity can be expressed as K = α ( 1 2 πd ) true( normald P true) 1 where dω is the shift in the Raman peak position of the A 1g mode concerning the change in incident laser power d P on the material surface, α is the first-order temperature coefficient, and d is the thickness of the material. Shen et al and many other researchers demonstrated that the thermal conductivity of perovskite materials is independent of the thickness ( d ) in the range of 90 to 400 nm. , As a result, the influence of thickness “ d ” on thermal conductivity ( K ) may be considered to be insignificant. Thus, the only quantities to examine are α and (dω/d P ).…”
Section: Resultsmentioning
confidence: 99%
“…Shen et al and many other researchers demonstrated that the thermal conductivity of perovskite materials is independent of the thickness (d) in the range of 90 to 400 nm. 61,62 As a result, the influence of thickness "d" on thermal conductivity (K) may be considered to be insignificant. Thus, the only quantities to examine are α and (dω/dP).…”
Section: Thermal Conductivitymentioning
confidence: 99%
“…Moreover, it is not clarified yet about how to tailor the specific phonon modes and strong phonon scattering in halide perovskites by using the engineering parameters, such as elements, compositions, phases, microstructures and even artificial patterns. [ 152 ] Such a knowledge will be also helpful for engineering carrier dynamics in optoelectronic devices.…”
Section: Discussionmentioning
confidence: 99%